INTERNATIONAL COUNCIL OF MUSEUMS ICOM - Kamilla Dilshodovna Kuralbayeva (Bright Mind Publishing, 2025)
Тhe article considers the role and influence of the International Council of Museums - ICOM, and its further development. Attention is paid to the issue of improving the qualifications of museum workers in museum and related areas of training.
Keywords: ICOM, museum sphere, museum business, research centers, cultural community.